Post pancreatic surgery complications; surgeon vs interventional radiologists - Mohammad Sohail Asghar; Mohammad Zohaib Asgher; Abdul Wahab; Jaweria Aslam; Zafarullah, Sadaf; Waheed, Rehman (Journal of the Pakistan Medical Association, 2023)
Even at high-volume centres, pancreatic resections are linked with a high rate of complications, as well as significant morbidity and mortality. In the management of these occurrences, a multidisciplinary approach is required, and interventional radiology plays an important role in the treatment of patients who develop post-surgical problems. The current review was planned to provide an overview of interventional radiological techniques that can be used to treat various types of problems following pancreatic resection. Percutaneous fluid collection drainage, percutaneous transhepatic biliary operations, artery embolisation, venous interventions, and fistula embolisation are feasible therapeutic alternatives with fewer problems than a re-look surgery. They also have a shorter hospital stay and faster recovery. Key Words: Embolization, interventional radiology (IR), pancreatic resection, postpancreatectomy hemorrhage, stent-graft.